2021
DOI: 10.1002/jso.26512
|View full text |Cite
|
Sign up to set email alerts
|

Application of technology to educational needs in surgery

Abstract: Innovations in surgical education follow advancing clinical technology. New surgical methods have prompted demand for systematic methods to leverage computing power and internet tools to achieve proficiency‐based training goals. Virtual reality, high‐fidelity patient simulation, web‐based resources to facilitate performance assessment, and telementoring have become mainstream practices, although patient outcomes benefits are not well studied. Remote virtual meeting and mentoring have had transformative effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…Although the use of VR and AR has been shown to be particularly useful for surgical education and training, [28][29][30] there are only a few studies in the literature that evaluate its application in patient education. Pandrangi et al 31 investigated the use of VR in patient education of abdominal aortic aneurysms; they found that 89% of participants agreed or strongly agreed that they felt better informed about their care, and 84% of patients agreed or strongly agreed that they felt more engaged in their health care.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of VR and AR has been shown to be particularly useful for surgical education and training, [28][29][30] there are only a few studies in the literature that evaluate its application in patient education. Pandrangi et al 31 investigated the use of VR in patient education of abdominal aortic aneurysms; they found that 89% of participants agreed or strongly agreed that they felt better informed about their care, and 84% of patients agreed or strongly agreed that they felt more engaged in their health care.…”
Section: Discussionmentioning
confidence: 99%
“…Genel olarak, cerrahi eğitimin tüm seviyelerinde hedef yetkin klinik uygulamaya ulaşmaktır. Bununla birlikte, teknolojik ilerlemeler, tıbbi bakım için gelen erişim, kalite ve güvenliğe dair talepler ve gelişen bir yetkinlik anlayışı, cerrahi eğitimdeki mevcut durum ve eğilimlere katkıda bulunan önemli ve birbiriyle bağlantılı itici güçler olmuştur [95].…”
Section: Tıp Eğitiminde Sanal Gerçeklik Kullanımıunclassified
“…Örneğin, 2020'de yapılan bir anket, yanıt veren eğitim programlarının %97'sinin cerrahi eğitiminde kapsamlı sanal konferansları benimsediğini ortaya koymuştur [127]. Bununla birlikte, uygulamalı eğitim olanaklarının kaybı ve stajyerlerin fiziksel ve duygusal esenliğine yönelik karmaşık güçlükler de dahil olmak üzere diğer zorluklar karşısında mevcut teknolojilerin yaygın oluşu tek başına kolay bir geçişi garanti etmemiştir [95].…”
Section: Güncel Görünüm Zorluklar öNeriler Ve öNgörülerunclassified